2020
DOI: 10.1021/acschemneuro.0c00414
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Inhibits Multiple Steps in the Amyloid Beta Toxicity Cascade

Abstract: Oligomeric β-amyloid peptide (Aβ) is one of the main neurotoxic agents of Alzheimer's disease (AD). Oligomers associate to neuronal membranes, forming "pore-like" structures that cause intracellular calcium and neurotransmitter dyshomeostasis, leading to synaptic failure and death. Through molecular screening targeting the C terminal region of Aβ, a region involved in the toxic properties of the peptide, we detected an FDA approved compound, gabapentin (GBP), with neuroprotective effects against Aβ toxicity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Also, to characterize the presence of oligomeric Aβ in the preparations used in all the experiments, we used transmission electron microscopy coupled to immunogold staining that showed the presence of spherical or disk‐shaped structures of Aβ ranging in sizes from 5 to 25 nm approximately (Figure S3c ). Furthermore, using this aggregation technique, together with WB, Transmission Electronic Microscopy and AFM analysis, we concluded that most of Aβ are in its soluble oligomeric form, from dimers to small protofibrils (González‐Sanmiguel et al., 2020 ; Peters et al., 2013 , 2016 ). More importantly, the acute extracellular application of these resulting Aβ species at low concentrations (0.5–1 μM) and dissolved in physiological solution produced an increase in intracellular calcium and synaptic transmission in hippocampal neurons allowing us to conclude that these species are diffusible and interact with cell membranes.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Also, to characterize the presence of oligomeric Aβ in the preparations used in all the experiments, we used transmission electron microscopy coupled to immunogold staining that showed the presence of spherical or disk‐shaped structures of Aβ ranging in sizes from 5 to 25 nm approximately (Figure S3c ). Furthermore, using this aggregation technique, together with WB, Transmission Electronic Microscopy and AFM analysis, we concluded that most of Aβ are in its soluble oligomeric form, from dimers to small protofibrils (González‐Sanmiguel et al., 2020 ; Peters et al., 2013 , 2016 ). More importantly, the acute extracellular application of these resulting Aβ species at low concentrations (0.5–1 μM) and dissolved in physiological solution produced an increase in intracellular calcium and synaptic transmission in hippocampal neurons allowing us to conclude that these species are diffusible and interact with cell membranes.…”
Section: Methodsmentioning
confidence: 86%
“…In general, they do not appear to be monomers or fibers, to a large extent. From previous studies, employing biochemical, transmission electronic microscopy, and AFM analysis (González-Sanmiguel et al, 2020;Peters et al, 2016Peters et al, , 2020, we concluded that most of Aβ are in its soluble oligomeric form, from dimers to small protofibrils. More importantly, we showed that the acute application of these resulting Aβ species, at low concentrations (0.5-1 μM), dissolved in physiological solution similar to the present study, produced increases in intracellular calcium and synaptic transmission in hippocampal neurons allowing us to conclude that these species are diffusible and interact with cell membranes.…”
Section: Iaβo Increased Neuronal Excitability Of Hippocampal Neurons In Vivo and In Vitromentioning
confidence: 84%
“…We previously reported that treatment (24 h) of hippocampal neurons with Aβ oligomers (AβO), but not monomers or fibers, reduced synaptic transmission evidenced by a large reduction in frequency of evoked and miniature currents, together with a number of presynaptic markers, that included SV2 (Parodi et al, 2010). In more recent studies, we have confirmed these original findings on the synaptoxicity of AβO and further characterized the toxic components of these Aβ assemblies by oligomerization time curves, characterization of dimer and tretramers and by atomic force microscopy that reported nanometric structures (González-Sanmiguel et al, 2020).…”
Section: Introductionmentioning
confidence: 52%
“…We observed that gabapentin was associated with a 39% reduced risk of AD (HR 0.61, 95% CI 0.58-0.64) in OneFlorida and a 28% reduced risk of AD (HR 0.72, 95% CI 0.70-0.74) in MarketScan. Previous research suggested possible benefit of gabapentin for behavioural and psychological symptoms of dementia in AD patients based on summarizing case reviews 22 , and revealed crucial role of gabapentin in the Amyloid Beta Toxicity Cascade 23 (See Supplementary Table 6 for review details). Our study showed one of the first large-scale RWD signals of gabapentin for AD.…”
Section: Resultsmentioning
confidence: 99%